Is this the ‘new normal’? A mixed method investigation of young person, parent and clinician experience of online eating disorder treatment during the COVID-19 pandemic - Catherine Stewart; Anna Konstantellou; Fatema Kassamali; Natalie McLaughlin; Darren Cutinha; Rachel Bryant-Waugh; Mima Simic; Ivan Eisler; Julian Baudinet (Journal of Eating Disorders, 2021)
Plain English summary Due to the COVID-19 pandemic specialist eating disorder treatment needed to quickly adapt to new technologies. All but urgent and crisis appointments needed to be delivered online. This study looked at what that was like for the young people, their parents and clinicians engaged in treatment in a large specialist eating disorder service in London, UK. Fifty-three young people with an eating disorder, 75 parents and 23 clinicians completed anonymous online surveys about their experience. Results showed that generally people were satisfied with treatment, the therapeutic relationship was maintained and most managed technological issues well. Four main themes were identified from responses to open ended free-text response questions. All three groups wrote about 1) making it work, 2) home as a therapeutic space, and 3) disrupted connection. The fourth theme, 4) into the future, came from parent and clinician responses only. These results have implications for ongoing care during the pandemic and for future implementation of virtual care in the treatment of young people with eating disorders. Particular issues arising are the trade-off between accessibility and the potential impact on the therapeutic relationship. There is also a need to make sure there is equal access to treatment in socially unequal societies.